2012
DOI: 10.5463/dcid.v23i3.167
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Exploratory Evaluation of the Frequency, Causes and Consequences of Rehabilitation Wheelchair Breakdowns delivered at a Paediatric Clinic in Mexico

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 26 publications
0
40
0
2
Order By: Relevance
“…More than 60% of users in a regional study from South Africa agreed that the wheelchair allowed satisfactory indoor and outdoor mobility (Visagie, Duffield & Unger 2015). Environmental barriers were not explored in any one of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…More than 60% of users in a regional study from South Africa agreed that the wheelchair allowed satisfactory indoor and outdoor mobility (Visagie, Duffield & Unger 2015). Environmental barriers were not explored in any one of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Caster failure modes found during wheelchair testing studies [29][30][31][32][33][34][35][36][37][38][39][40][41] and field trials [11,13,14,[47][48][49] were compiled. They were manually screened for inclusion in C-FIT by a wheelchair testing engineer with 7 years of testing experience and a technician with over 20 years of experience in wheelchair maintenance.…”
Section: Initial C-fit Developmentmentioning
confidence: 99%
“…Wheelchairs are known to experience frequent repairs and breakdowns. Product evaluation studies from Kenya, India and Mexico have reported breakdowns and multiple part failures with casters, brakes, seats and tires within 2-3 months to two years of wheelchair use [11][12][13][14][15]. In a series of cross-sectional survey studies conducted in the United States, about 44-64% of wheelchair users reported at least one breakdown within 6months of wheelchair use and nearly one-third of them suffered immediate consequences such as being stranded or injured and missing school, work or appointments [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations